KESEHATAN MENTAL, PENGAWASAN MELEKAT DAN PERILAKU KORUPSI - ', Nurkholis (Jurnal Ilmu Administrasi Negara, 2016)
Mental Health and Behavior Monitoring Fitted Corruption. This study aims to identify and analyze the extent of the influence of mental health and oversight attached to corruption. This research is a descriptive research with quantitative approach. The population in this study were employees of the Faculty of Agriculture, University of Riau administration and teachers or lecturers. Data collection techniques were questionnaires, observations and interviews. Analysis of data through multiple regression statistical test program with the help of Statistical Product and Service Solution (SPSS) 16.5 for windows. The results showed that there are significant negative and significant correlation between mental health and oversight attached to the corruption of 66.7%. That is, the healthier the better mental and oversight attached to the action for corruption is getting low. Conversely, if the unhealthy mental and worse levels of supervision attached to the action for corruption is increasing.